Pengaruh Desentralisasi Dan Ketidakpastian Lingkungan Terhadap Kinerja Manajerial Dengan Kualitas Sistem Informasi Akuntansi Manajemen Sebagai Variabel Intervening Pada PT. Perkebunan Nusantara IV Medan - Sara Wandari; Maya Sari; Zulia Hanum (CV. ITTC INDONESIA, 2024)
This research aims to test and analyze the effect of decentralization and environmental uncertainty on managerial performance with the quality of the management accounting information system as an intervening variable at PT. Perkebunan Nusantara IV Medan. Where variables are measured using an ordinal scale. The data collection method was carried out by interviews, with a list of questions (questionnaire). The population and sample of this research were 44 PT managers. Perkebunan Nusantara IV Medan. The types of data used in this research are primary and secondary data by analyzing and testing the inner model and outer model with the help of Structural Equation Model-Partial Least Square (SEM-PLS) data processing software. test findings show that: (1) decentralization has an effect on managerial performance (2) environmental uncertainty has an effect on managerial performance (3) decentralization has an effect on the quality of management accounting information systems (4) environmental uncertainty has an effect on the quality of management accounting information systems (5) system quality management accounting information influences managerial performance (6) the quality of management accounting information systems can mediate the relationship between decentralization and managerial performance (7) the quality of management accounting information systems can mediate the relationship between environmental uncertainty and managerial performance.